PENGARUH ENZIM BROMELIN DAN WAKTU INKUBASI PADA PROSES HIDROLISIS IKAN LEMURU MENJADI KECAP - Taufik Iskandar; Desi Arena Widyasrini (Universitas Tribhuwana Tunggadewi, 2009)
The process of making fish ketchup used to take quite long time. There are many efforts to improve the technology; one of them is using proteolitic enzime as a catalist that has a function of breaking down protein into asam aminos. Anyway, the problem is that the pure proteolistic enzime costs very expensive. This research was trying to find the way to easily and less costly make proteolitic enzime, and highly to dissolve nitrogen as well. The extract of pineapples was then used in the hydrolisis process because it is known that it contains high quantity of bromelin enzime act as proteolitic enzime. A kind of fish called lemuru was choosen as a raw material of producing ketchup in this observation due to the high content of protein. The hydrolisis process is conducted in the room temperature by adding the extract of pineapples in some variety of concentration (6, 8, 10%) and using 8, 10, and 12 hours incubation time. The best result was at the concentration of 8% pineapple axtract and 10 hours incubation time. It produced totally 1,0233% nitrogen, contained of 0,86% dissolvent nitrogen, 27,5% dissolvent solid substance, 17% liquid volume and viscocity of 41,364%